Electrocution threatens the viability of populations of the endangered Bonelli's eagle (Aquila fasciata) in Southern Europe. (November 2015) - Hernández-Matías, Antonio; Real, Joan; Parés, Francesc; Pradel, Roger
Abstract: Electrocution on power lines negatively affects a wide range of groups of birds. Nevertheless, the overall demographic consequences of electrocution are still poorly understood. Typically, little demographic data is available for endangered species and so approaches aimed at guiding conservation measures that bear in mind this uncertainty are urgently required. In the present study, we develop a procedure based on population modeling that is useful both for obtaining unbiased estimates of mortality caused by electrocution and for estimating the mitigation effort required to restore threatened populations — even if uncertainty regarding parameter estimates exists. We used as a case study the Bonelli's eagle ( Aquila fasciata ) population in the NE Iberian Peninsula. Firstly, we used multievent models to estimate mortality while accounting for imperfect detection and uncertainty in state assignment. The fraction of mortality caused by electrocution ( α ) was not directly estimable from the multievent models and so to estimate this parameter we developed a method that used in addition basic monitoring information. Accordingly, α was estimated at 0.26 and 0.62 for, respectively, territorial and non-territorial individuals in the period 2008–2014. Secondly, we applied viability analysis to gauge the effort that would be required to mitigate electrocution and guarantee population self-sustainability. Our results highlight the fact that even low levels of electrocution can drive a local population to extinction. Overall, our study establishes a framework for estimating the demographic effects of electrocution and provides conservation managers with information on the effort needed to mitigate human-induced mortality and restore threatened populations. Graphical abstract: Highlights: We developed a procedure for estimating electrocution effects on bird demography. We applied the method in one Bonelli's eagle population in Southern Europe. Low levels of electrocution can drive populations of long-lived birds to extinction. Our framework allows quantifying the mitigation effort required to restore populations.